2016
DOI: 10.1002/mbo3.328
|View full text |Cite
|
Sign up to set email alerts
|

The programming effects of nutrition‐induced catch‐up growth on gut microbiota and metabolic diseases in adult mice

Abstract: Substantial evidence indicated that catch‐up growth could increase the susceptibility to obesity, insulin resistance, and type 2 diabetes mellitus in adulthood. However, investigations into the “programming” effects of catch‐up growth on gut microbiota in the offspring are limited. C57/BL6 mice were fed on either low protein (LP) or normal chow (NC) diet throughout gestation and lactation. Then, the offspring were randomly weaned to either NC or high fat (HF) diet until 32 weeks of age, generating four experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…A loss of microbial diversity in the intestine is also shown in several human intestinal and extraintestinal disorders, including inflammatory bowel disease (IBD), colorectal cancer (CRC), chronic liver diseases, type 2 diabetes, and asthma (Tilg et al, 2018 ). In the present study, the core gut microbiome at the phylum level in uninfected and infected mice was dominated by Firmicutes, Bacteroidetes and Proteobacteria, which are commonly found in the mouse model (Zheng et al, 2016a , b ; Deng et al, 2018 ; Kim et al, 2019 ). Significant differences were found before and after infection.…”
Section: Discussionmentioning
confidence: 50%
“…A loss of microbial diversity in the intestine is also shown in several human intestinal and extraintestinal disorders, including inflammatory bowel disease (IBD), colorectal cancer (CRC), chronic liver diseases, type 2 diabetes, and asthma (Tilg et al, 2018 ). In the present study, the core gut microbiome at the phylum level in uninfected and infected mice was dominated by Firmicutes, Bacteroidetes and Proteobacteria, which are commonly found in the mouse model (Zheng et al, 2016a , b ; Deng et al, 2018 ; Kim et al, 2019 ). Significant differences were found before and after infection.…”
Section: Discussionmentioning
confidence: 50%
“…The amplicons were extracted and purified from a 1% agarose gel in accordance with the manufacturer’s instructions using a AxyPrep DNA Gel Extraction Kit (Axygen Biosciences company, Union City’s, CA, USA) and using Quanti Fluor™-ST (Promega, USA) for quantification based on the previous describe methods (Zheng et al 2016 ). Uqimolar purified amplicons were combined and paired-end sequenced according to standard protocols (2 × 250) of the Illumina MiSeq platform (Yan et al 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…The early developmental environment has a lasting memory effect that lasts the whole life, called “metabolic memory,” which has been widely accepted and recognized by the academic community. Since Barker first discovered that people with lower birth weight had higher death rates from ischemic heart disease [51], large number of clinical studies [5257] and animal experiments [7, 5863] have demonstrated that adverse early-life exposures, such as nutrient restriction or overnutrition, gestational diabetes and maternal obesity and HFD, significantly increased the risk of developing metabolic diseases in later life. However, the precise underlying mechanism by which deciphers the “metabolic memory” is still not fully understood.…”
Section: Disorders Of Circadian Rhythm Might Be An Important Mechamentioning
confidence: 99%
“…We previously reviewed the role of gut microbiota in the effects of maternal obesity on metabolism of offspring and indicated that gut microbiota might be an essential programing factor for the increased risk of metabolic disorders in later life induced by adverse nutritional environments in early life [85]. Our research [7] and other studies [8689] have found that the composition and diversity of gut microbiota changed significantly, which was accompanied by metabolic disorders in later life, after exposure to adverse nutritional environments in early life. An animal experiment has shown that alpha diversity was significantly decreased in the gut microbiota of mice from HFD-fed dams compared with the chow diet-fed dams [9].…”
Section: The “Gut Microbiota-circadian Clock Axis” May Be the Key mentioning
confidence: 99%
See 1 more Smart Citation